A new data logger based on Raspberry-Pi for Arctic Notostraca locomotion investigations. (November 2017) - Pasquali, V.; D'Alessandro, G.; Gualtieri, R.; Leccese, F.
Highlights: Motor activity detection based on Raspberry-Pi and infrared sensors. Device has been tested in real experimental conditions in Arctic environment. Python has been used as programming language for the scripts of the Raspberry-Pi. Low cost and small sizes are won challenges essential for remote sites. Preliminary data on biological rhythms of Arctic Notostraca have been collected. Abstract: A new data logger based on Raspberry-Pi to monitor the locomotion of Arctic invertebrates has been made, tested and deployed in field. The device uses infrared sensors to check in vivo the invertebrates picking up the locomotor activity, data are collected for the analysis. Thanks to the Raspberry Pi capabilities and features, the instrument proved to be suitable for extreme scenarios such as the polar environment, offering good performances obtained at a very low price. Preliminary test made in field have demonstrated its reliability. Some experimental considerations and the trend of the biological rhythms of the tadpole shrimp's locomotor activity are also discussed.